Zebrafish bio-assay guided isolation of human acetylcholinesterase inhibitory trans-tephrostachin from Tephrosia purpurea (L.) Pers. (20th November 2018) - Pitchai, Arjun; Nagarajan, Nagasundaram; Vincent, Samuel Gnana Prakash; Rajaretinam, Rajesh Kannan
Highlights: First report on the isolation of acetylcholinesterase inhibitory trans - tephrostachin from Tephrosia purpurea (L.) Pers. Enzyme inhibition mechanism favored the mixed type for both zebrafish brain extract and human acetyl cholinesterase. In silico studies of trans- tephrostachin confirmed the better binding affinity and efficacy than donepezil and galanthamine. Abstract: An acetylcholinesterase inhibitory compound was isolated from Tephrosia purpurea (L.) Pers. by zebrafish brain based bioassay guided isolation and predicted as trans -tephrostachin.Enzyme kinetics studies (Line weaver-Burk plots and Michaelis Menten equation) favored the reversible / mixed type, with the inhibition constant ( Ki ) of 53.0 ± 7.4 μM in zebrafish brain (IC50 value of 39.0 ± 1.4 μM). However, the inhibition constant (Ki) was found to be 36.0 ± 0.4 μM with IC50 value of 20.0 ± 1.0 μM, whereas donepezil showed 3.2 ± 0.3 μM with the IC50 value of 0.12 ± 0.04 μM for human acetylcholinesterase. Further, the molecular docking, dynamics and simulation for trans -tephrostachin obtained better binding affinity and efficacy than commercial drugs donepezil and galanthamine. Hence, the isolated compound trans – tephrostachin from T. purpurea shall be further considered for the development of potential drug for the counteraction of Alzheimer's disease progression.